2002
DOI: 10.1159/000067550
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amniotic Membrane Transplantation and Mitomycin C on Wound Healing in Experimental Glaucoma Surgery

Abstract: Purpose: To evaluate the effects of mitomycin C and amniotic membrane transplantation on the modulation of wound healing after glaucoma filtration surgery. Methods: Trabeculectomy was performed in 3 groups of 10 rabbit eyes each. Sponges soaked in mitomycin C were applied to the first group, and amniotic membranes were transplanted around the scleral flap in the second group; the third group was the control. The arithmetic means of fibroblast and macrophage numbers per square centimetre were calculated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…25 Amniotic membrane transplantation, which showed suppression of wound healing in experimental filtration surgery in agreement with its ability to down regulate TGFß signaling, 26 may also have a space-keeping effect as a mechanical barrier.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…25 Amniotic membrane transplantation, which showed suppression of wound healing in experimental filtration surgery in agreement with its ability to down regulate TGFß signaling, 26 may also have a space-keeping effect as a mechanical barrier.…”
Section: Discussionmentioning
confidence: 82%
“…[8][9][10][11][12][13] Recently, to avoid such postoperative complications caused by MMC and 5-FU, various anti-scarring chemicals and mechanical adhesion barriers have been used in glaucoma filtration surgery in animal models. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Although favorable results were reported, no alternative methods to MMC or 5-FU treatment have been widely adapted until now.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that transplantation of a single (Fujishima et al, 1998;Lu and Mai, 2003;Yue et al, 2003;Drolsum et al, 2006) or folded (Bruno et al, 2006;Eliezer et al, 2006) sheet of AM under the scleral flap (Fujishima et al, 1998;Yue et al, 2003;Drolsum et al, 2006;Bruno et al, 2006), and/or under the conjunctiva (Yue et al, 2003;Drolsum et al, 2006;Bruno et al, 2006;Eliezer et al, 2006), with additional MMC (Fujishima et al, 1998;Drolsum et al, 2006;Bruno et al, 2006), reduces IOP in eyes with refractory glaucoma. Experimental rabbit studies demonstrated that the AM, inserted under the scleral flap, achieves the same reduction of subconjunctival fibroblasts and macrophages around the trabeculectomy sites as that achieved by MMC (Demir et al, 2002;Wang et al, 2005), as well as reduces the number of fibroblasts at trabeculectomy sites when inserted under the scleral flap even without MMC (Zhong et al, 2000;Barton et al, 2001). …”
Section: Preliminary Studiesmentioning
confidence: 99%
“…Besides these, β-radiation, amniotic membrane, and even photodynamic therapy have been used for the success of trabeculectomy [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%